Kinesiology tape increases muscle tone, stiffness, and elasticity: effects of the direction of tape application - Lopes, Mário (2022)
The claim that the effects of kinesiology tape are different depending on the direction of tape application needs to be clearly ascertained. This study aimed to determine the immediate effects of two forearm kinesiology tape applications on muscle tone, stiffness, and elasticity of young individuals. Thirty-nine participants (15 men and 24 women) were randomized (1:1:1) to: the facilitatory group, receiving kinesiology tape applied from origin to insertion; the inhibitory group, receiving kinesiology tape applied from insertion to origin; or, a control group, without any intervention. The mechanical properties - tone, elasticity, and stiffness - of the forearm muscles were measured with a handheld mechanical impulse-based myotonometric device before and 30 min after the kinesiology tape application. Only the application of kinesiology tape from origin to insertion significantly increased muscle tone [16.6 (2.5) to 17.4 (3.5) Hz, p = 0.036], stiffness [318.3 (52) to 355.0 (87) N/m, p = 0.004], and elasticity [0.98 (0.1) to 1.10 (0.1), p = 0.023]. No changes were observed in both inhibitory kinesiology tape and the control group. In conclusion, kinesiology tape application has different effects depending on the direction of the taping application. The facilitatory tapping increased muscle tone, elasticity, and stiffness.